Taito adrik, a new harvestman species from the Área de Conservación Privada Panguana, Peruvian Amazonia (Opiliones: Laniatores: Cosmetidae) - Friedrich, Stefan; Lehmann, Tobias (Zootaxa, 2020)
A new species of the cosmetid harvestman genus Taito Kury & Barros 2014 is described from the Área de Conservación Privada (ACP) Panguana, Peruvian Amazonia, which extends the distribution range of the genus to the south-west. The herein described species Taito adrik sp. nov. differs from all other known species of the genus by the distinct shape of the equuleus, the armature of leg IV in males, and the structure of male genitalia, in combination with features of the chelicerae and the anal operculum. In addition, COI barcodes of the new species are provided.